2019
DOI: 10.3758/s13423-019-01656-z
|View full text |Cite
|
Sign up to set email alerts
|

Does interference between self and other perspectives in theory of mind tasks reflect a common underlying process? Evidence from individual differences in theory of mind and inhibitory control

Abstract: Theory of mind (ToM), the ability to understand that other agents have different beliefs, desires, and knowledge than oneself, has been extensively researched. Theory of mind tasks involve participants dealing with interference between their self-perspective and another agent's perspective, and this interference has been related to executive function, particularly to inhibitory control. This study assessed whether there are individual differences in self-other interference, and whether these effects are due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 77 publications
(106 reference statements)
1
30
1
1
Order By: Relevance
“…As such, rather than observing a negative impact owing to the avoidance of avatar liking, when the director's preference was to approach the target object (liking target, disliking competitor), we observed a facilitation in performance, with accuracy rates for these conditions higher than in previous studies (e.g. Qureshi Monk, Samson & Apperly, 2019;Apperly et al, 2010).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…As such, rather than observing a negative impact owing to the avoidance of avatar liking, when the director's preference was to approach the target object (liking target, disliking competitor), we observed a facilitation in performance, with accuracy rates for these conditions higher than in previous studies (e.g. Qureshi Monk, Samson & Apperly, 2019;Apperly et al, 2010).…”
Section: Discussioncontrasting
confidence: 77%
“…Inhibitory control, the ability to stop a dominant response, has been linked to performance the Director task (Qureshi, Monk, Samson & Apperly, 2019;Symeonidou, Dumontheil, Chow & Breheny, 2016). Its role may be to allow participants to inhibit their salient self-perspective to take the belief and knowledge of the director into account.…”
Section: Introductionmentioning
confidence: 99%
“…Brain regions involved in ToM include superior temporal sulcus, temporal poles, medial prefrontal cortex, temporoparietal junction, and posterior cingulate/precuneus (Schurz et al, 2014 ). Additionally, ventromedial prefrontal cortex and temporoparietal junction are implicated in self/other processing and judgments (Denny et al, 2012 ) and it has been suggested that overcoming self–other interference and ToM are deeply integrated processes (Qureshi et al, 2020 ). Moreover, simulating others has been shown to influence self-knowledge, with trait and memory measures becoming similar to a simulated other after adopting their perspective (Meyer et al, 2019 ).…”
Section: Theory Of Mind and Empathymentioning
confidence: 99%
“…Nevertheless, the current results should be viewed in light of the potential limitations of within-subject testing, caused by possible practice or familiarity effects caused by repeat testing. Post-hoc power analyses suggest that the power to detect the observed effect sizes was 0.97 (Faul et al, 2009), although a more well powered and pre-registered study (while the study was not preregistered (Munafò et al, 2017), the data are available on request) should be conducted in order to enable stronger inferences and conclusions (Zwaan et al, 2017).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%